Analysis of drivers and constraints in the Kansas grape and wine industry - Carter, Elizabeth (Kansas State University, 2021)
In 1985, The Kansas Farm Winery Act was passed, allowing for the sale and manufacture of wine in the state for the first time since prohibition. In the 35 years since the legalization of Kansas produced wine the market has grown to include over 50 wineries, and generating over $800M in revenue (Wine America, 2017). While the market is growing, interviews from both wine makers and producers suggest that the market growth is constrained by a number of factors (Derksen Schroeder, 2016; Stramel, 2015; Voorhis, 2014). To expand the industry, the stakeholders need to understand the potential drivers and constraints related to resource availability, policy framework, and supply chain governance. This study utilizes a combination of quantitative and qualitative methods to evaluate these constraints. A life cycle analysis was done to evaluate the water resources needed to support the grape production process. A case study method was used to evaluate the policy framework that could be impacting the growth of the market. Transaction Cost Economics framework was used to evaluate the effectiveness of various vertical coordination strategies at the producer-processor interface of grape/wine supply chain. Upon our analysis we found that grape vines require less water resources than more commonly grown crops in the area. In addition, grape vines can result in profits per acre of $1,062 per acre while the competing crops result in profits of approximately $363.76. This suggests that wine grapes could be a valuable asset to those looking to invest in a crop that is less dependent on available water resources. The case study of the policies impacting the market lead to the hypothesis that the constraining factor in market growth could be the product composition minimum established in the Kansas Farm Winery Act. When more recent data becomes available this hypothesis can be tested. When accounting for the various forms of asset specificity associated with the production of grapes and wine, our Transaction Cost Economics framework suggests that an equity based alliance could be a more effective governance structure than the spot market or vertical integration. Further study is needed to evaluate this hypothesis.
Keywords: Grape; Wine; Transaction costs; Supply chain